2021
DOI: 10.1016/j.jesp.2021.104228
|View full text |Cite
|
Sign up to set email alerts
|

Climate change threats increase modern racism as a function of social dominance orientation and ingroup identification

Abstract: Climate change threats increase modern racism as a function of social dominance orientation and ingroup identification Fatih Uenal 1,2

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 49 publications
5
14
1
Order By: Relevance
“…Resembling findings in the intraspecies domain among humans (conspecific: intragroup, intergroup relations), previous studies have shown an inverse relationship between SDO and pro-social attitudes towards non-human animals and the natural environment (e.g., Becker et al, 2019; Costello & Hodson, 2010; Dhont & Hodson, 2014; Dhont et al, 2016; Everett et al, 2019; Graça, 2020; Hoffarth et al, 2019; Hyers, 2006; Jylhä & Akrami, 2015; Milfont et al, 2013; Milfont & Sibley, 2014). For example, previous research has consistently shown that SDO is associated with lower levels of environmentalism (e.g., Milfont et al, 2018), with climate change denial (e.g., Jylhä et al, 2020), and also with decreased climate change threat perceptions (Uenal, Sidanius, Roozenbeek, & van der Linden, 2020).…”
Section: Exploiting Nature Animals and Humans: A Social And Ecologica...mentioning
confidence: 99%
See 3 more Smart Citations
“…Resembling findings in the intraspecies domain among humans (conspecific: intragroup, intergroup relations), previous studies have shown an inverse relationship between SDO and pro-social attitudes towards non-human animals and the natural environment (e.g., Becker et al, 2019; Costello & Hodson, 2010; Dhont & Hodson, 2014; Dhont et al, 2016; Everett et al, 2019; Graça, 2020; Hoffarth et al, 2019; Hyers, 2006; Jylhä & Akrami, 2015; Milfont et al, 2013; Milfont & Sibley, 2014). For example, previous research has consistently shown that SDO is associated with lower levels of environmentalism (e.g., Milfont et al, 2018), with climate change denial (e.g., Jylhä et al, 2020), and also with decreased climate change threat perceptions (Uenal, Sidanius, Roozenbeek, & van der Linden, 2020).…”
Section: Exploiting Nature Animals and Humans: A Social And Ecologica...mentioning
confidence: 99%
“…Previous studies indicate that a sense of feeling threatened by climate change seems pivotal for increasing pro-social and pro-environmental attitudes and behaviors aimed at mitigating the consequences of global warming (e.g., van der Linden et al, 2015). However, previous research also shows that individuals differ greatly in their climate change risk and threat perceptions (e.g., Hoffarth & Hodson, 2016; van der Linden, 2015; Uenal, Sidanius, Roozenbeek, & van der Linden, 2020). Therefore, a better understanding of individual difference variables influencing risk and threat perceptions seems important to increase public engagement with and individual responsibility to act on climate change.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, in response to climate change threat exposure and in accordance with sharpening of authoritarian attitudes, those with authoritarian predispositions may develop greater preference for a response to climate change that is rooted in ecofascist ideologies (Taylor 2019), such as "addressing" the alleged overpopulation or the alleged immigration problem. Recent studies show, climate change threat increases intergroup threat perceptions and racism (Uenal et al 2021).…”
Section: Discussionmentioning
confidence: 99%